1990
DOI: 10.2331/suisan.56.783
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Adonis aestivalis as a dietary pigment source for rainbow trout salmo gairdneri.

Abstract: The flower, Adonis aestivalis and its pigment extract were fed to two different sizes of rainbow trout Salmo gairdneri at a level of 10mg total pigment/100g diest.The larger fish (average weitht 400g) were fed the pigment extract for 8 weeks. In the males, carotenoids were mainly deposited in the skin and a samll amount was found in the flesh. However, in the females, a relatively high level of carotenoids was detected in the flesh.The smaller fish were fed the diets containing Adonis flower petals or its pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The accumulation of carotenoids with 3,4-didehydro-b-rings in cells of E. coli containing pAC-BETA and one or both of the cbfd cDNAs ( Figure 3B) may simply be a consequence of the nonnative environment. Carotenoids with 4-hydroxy-b-rings are the predominant pigments in the flowers of three species of Adonis with yellow petals (Czygan, 1969), and small amounts of such carotenoids have been detected in the red, ketocarotenoidcontaining flower petals of A. aestivalis (Neamţu et al, 1966;Kamata et al, 1990) as well, but carotenoids with 3,4-didehydrob-rings have not been reported to be present in the flowers of any species of Adonis. The enzymes encoded by the hbfd1 and hbfd2 cDNAs will therefore be designated as carotenoid 4-hydroxy-b-ring 4-dehydrogenases (HBFDs).…”
Section: The Enzymes That Convert B-carotene Into Astaxanthin In Adonmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of carotenoids with 3,4-didehydro-b-rings in cells of E. coli containing pAC-BETA and one or both of the cbfd cDNAs ( Figure 3B) may simply be a consequence of the nonnative environment. Carotenoids with 4-hydroxy-b-rings are the predominant pigments in the flowers of three species of Adonis with yellow petals (Czygan, 1969), and small amounts of such carotenoids have been detected in the red, ketocarotenoidcontaining flower petals of A. aestivalis (Neamţu et al, 1966;Kamata et al, 1990) as well, but carotenoids with 3,4-didehydrob-rings have not been reported to be present in the flowers of any species of Adonis. The enzymes encoded by the hbfd1 and hbfd2 cDNAs will therefore be designated as carotenoid 4-hydroxy-b-ring 4-dehydrogenases (HBFDs).…”
Section: The Enzymes That Convert B-carotene Into Astaxanthin In Adonmentioning
confidence: 99%
“…The red yeast Xanthophyllomyces dendrorhous (Luká cs et al, 2006) and the green alga H. pluvialis (Del Campo et al, 2007) currently serve as the principal biological sources, but astaxanthin obtained from X. dendrorhous and H. pluvialis is considerably more costly to produce than is the synthetic pigment (Luká cs et al, 2006;Schmidt et al, 2011), and strain improvements and/or modifications of culture conditions seem likely to yield only incremental reductions in the cost of production. A. aestivalis has itself received some attention as a prospective biological source of astaxanthin (Kamata et al, 1990), with efforts made to develop improved strains (Rodney, 1995;Rayton et al, 2006), but the relatively small flowers of this plant render it ill suited for commercial production.…”
Section: Prospects For the Biological Production Of Astaxanthinmentioning
confidence: 99%
“…Furthermore, the feeding of plant pigment sources in some species often produces undesirable yellowish coloration due to the lack of red xanthophylls (Kamata et al, 1990). In the case of salmonid fish, for example, a limitation in the use of carotenoidrich feed ingredients of plant origin is due to the fact that they contain pigments that do not produce the desired color quality of salmon flesh, as is naturally provided by astaxanthin in the aquatic environment.…”
Section: Carotenoid-rich Feed Ingredientsmentioning
confidence: 99%
“…have low bioavailability and are poorly hydrolyzed in the digestive tract of fish. Overall, the astaxanthin concentration of dehydrated petals of Adonis annua is approximately 11,000 mg/kg (approximately 75% of the total carotenoids) and the flowers of A. aestivalis contain around 1600 mg/kg (approximately 80% of the total carotenoids) (Maoka et al, 2011;Kamata et al, 1990;Renstrøm et al, 1981a).…”
Section: Carotenoid-rich Feed Ingredientsmentioning
confidence: 99%
“…Among these are synthetic astaxanthin (Choubert and Heinrich, 1993;Wathne et al, 1998); synthetic canthaxanthin (Torrisen and Naevdal, 1984;Choubert and Heinrich, 1993); astaxanthin from Adonis aestivalis (Kamata et al, 1990); astaxanthin from Phaffia rhodozyma (Binkowski et al, 1993;Choubert et al, 1995); xanthophylls from Tagetes erecta (VernonCarter et al, 1994); carotenoids from red pepper (Yanar et al, 1998); carotenoids from oleoresin paprika (Akhtar et al, 1999); astaxanthin from Haematococcus pluvialis (Sommer et al, 1991); astaxanthin from Rhodobacter capsulatus (Pradal, 1994); and astaxanthin from Pleuroncodes planipes (Coral et al, 1998). When comparative studies were conducted, higher levels of total carotenoid and coloration in trout muscle were found in groups fed synthetic astaxanthin (Roche Carophyll Pink) compared with the natural carotenoids from different sources.…”
Section: Introductionmentioning
confidence: 99%